VALUE-BASED EDUCATION AS A RESPONSE TO INDIVIDUALISM IN A MULTICULTURAL ENVIRONMENT - Lu’Luul Mukarromah; Hasan Baharun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research is motivated by the increasing symptoms of individualism in educational environments that threaten the values of togetherness, empathy, and social solidarity of students, especially in the context of a multicultural society. Islamic Religious Education (PAI) is presented as a value instrument to respond to this phenomenon through a Value-Based Education approach that emphasizes the integration of values, character, and learning experiences. The focus of this research is to describe the process of integrating Islamic values in reducing individualism and shaping the social character of students in a multicultural environment. This research uses a case study method conducted at the Islamic Book Deliberation Institute of Nurul Jadid Islamic Boarding School in the Al-Hasyimiyah region. Data collection techniques include observation, in-depth interviews, and documentation. The results show that the implementation of Value-Based Education through the stages of clustering individualism, planning individualism, applying approach, and approach evaluation successfully reduced the level of individualism of students from an egoistic orientation to social empathy. Internalization of multicultural Islamic values is implemented through four dimensions, namely curriculum integration, explicit teaching, social project-based learning, and the formation of an inclusive school culture. The transformation of student character is evident in the change in attitude from apathetic to participatory and from self-orientation to social orientation. The implications of this research confirm that Value Based Education is not only effective as a pedagogical approach, but also strategic in building collective awareness, empathetic character, and social resilience amidst the current of individualism in a multicultural society.